alguien me ayuda porfavor
gracias u.u
Adjuntos:
![](https://es-static.z-dn.net/files/d3e/35f3bdba96f15e1c088c2d6c05881b83.jpg)
PascualDavid:
¿Quieres las 3?
Respuestas
Respuesta dada por:
1
Te ayudo con la primera:
Si a*b = (b*a)²
entonces:
![a*b=(a*b)(a*b) \\ \frac{a*b}{a*b}=a*b \\ 1=a*b \\ \\ (1*2)^2+(2*3)^3+(3*4)^4+...+(10*11)^{11}=\\1^2+1^3+1^4+...+1^{11}=10 a*b=(a*b)(a*b) \\ \frac{a*b}{a*b}=a*b \\ 1=a*b \\ \\ (1*2)^2+(2*3)^3+(3*4)^4+...+(10*11)^{11}=\\1^2+1^3+1^4+...+1^{11}=10](https://tex.z-dn.net/?f=a%2Ab%3D%28a%2Ab%29%28a%2Ab%29+%5C%5C++%5Cfrac%7Ba%2Ab%7D%7Ba%2Ab%7D%3Da%2Ab+%5C%5C+1%3Da%2Ab+%5C%5C+++%5C%5C+%281%2A2%29%5E2%2B%282%2A3%29%5E3%2B%283%2A4%29%5E4%2B...%2B%2810%2A11%29%5E%7B11%7D%3D%5C%5C1%5E2%2B1%5E3%2B1%5E4%2B...%2B1%5E%7B11%7D%3D10+)
Opción D
Saludos!
Si a*b = (b*a)²
entonces:
Opción D
Saludos!
Preguntas similares
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años